Akulturasi budaya Islam Nusantara: Merajut tradisi dan modernitas menjadi satu kesatuan - Annabila, Naela Ameilia; Ghozi, Ahmad; Putri, Tisya Aprilina Ardian; Ramadani, Ero Kurnia (Maliki Interdisciplinary Journal, 2024)
The acculturation of the Nusantara region with Islamic teachings is a complex phenomenon resulting in a unique blend of local traditions and Islamic values, influencing various aspects of life such as traditions, arts, and architecture. This article explores the roles of important figures like Wali Songo and Sultans/Rajas in this process and examines the impact of this assimilation in creating a distinctive Nusantara Islamic culture along with its challenges. The study aims to provide a deep understanding of the assimilation process and its relevance today, highlighting how the Nusantara people maintain their cultural identity while adopting Islamic teachings. Through a literature-based approach, the article analyzes key themes and concepts in cultural assimilation and offers strategies for preservation in the era of modernization and globalization. The findings reveal that this assimilation not only enriches local culture but also strengthens the Islamic identity of the Nusantara people, creating harmony between local traditions and religion, while demonstrating dynamic and sustainable adaptation. This assimilation also illustrates how culture and religion can collaborate to create a richer and more diverse society.